ChemInform Abstract: Chemical Vapour Deposition of CNTs Using Structural Nanoparticle Catalysts. Issue 20 (25th April 2013) - Ayre, G. N.; Uchino, T.; Mazumder, B.; Hector, A. L.; Smith, D. C.; Ashburn, P.; de Groot, C. H.; Hutchison, J. L.
Abstract Review: (CNT: carbon nanotube) 74 refs.